Bosch Automotive Electrics and Automotive Electronics : Systems and Components, Networking and Hybrid Drive - Robert, Bosch GmbH (Bosch Professional Automotive Information, 2014)
The significance of electrical and electronic systems has increased considerably in the last few years and this trend is set to continue. The characteristics feature of innovative systems is the fact that they can work together in a network. This requires powerful bus systems that the electronic control units can use to exchange information. Networking and the various bus systems used in motor vehicles are the prominent new topic in the 5th edition of the "Automotive Electric, Automotive Electronics" technical manual. The existing chapters have also been updated, so that this new edition brings the reader up to date on the subjects of electrical and electronic systems in the motor vehicle. Content Electrical and electronical systems - Basic principles of networking - Examples of networked vehicles - Bus systems - Architecture of electronic systems - Mechatronics - Elektronics - Electronic control Units - Software - Sensors - Actuators - Hybrid drives - Vehicle electrical system - Starter battery - Alternator - Starting system - Electromagnetic compatibility - Circuit diagrams Target audience Automotive engineers completing further education Automotive foremen and mechanics in automotive repair shops Teachers and lecturers in vocational schools Students at colleges and technical schools and all those interested in automotive engineering Publisher Bosch is one of the world's leading suppliers to the automotive industry. The large number of applications for patents and utility models is impressive proof of the company's leading position in automotive engineering.